KETERLIBATAN PUSTAKAWAN DALAM PENGELOLAAN JURNAL ILMIAH ELEKTRONIK LEMBAGA - Farli Elnumeri; Wahid Nashihuddin (Jurnal IPI (Ikatan Pustakawan Indonesia), 2017)
Journal management requires the seriousness and high commitment of the institution that publishes it. One of the professions involved in managing a journal is the librarian. This article discusses the active role of librarians in the management and publishing of journals in Indonesia in accordance with their main tasks and functions in their respective institutions. The method used is descriptive-qualitative that comes from the experience and observation of the author, knowledge sharing, and literature study. The role of librarians in managing journals that become the parent institution may vary. This condition depends on the internal situation in each institution. There are two roles that are usually administered by librarians, namely the administration of journals and administrators of electronic journals. Journal administrations are usually called managing editors, editorial secretaries or managing editors. The administrator of the journal is usually more to information technology related to the journal. These two roles can be said to be the heart of journal management. There are some librarian activities / work that can be claimed as a credit score when becoming a journal manager, including: creating keywords, compiling an article index, compiling an article abstract, and compiling a journal writer directory. Activities such as making secondary literature such as indexes, abstract bundles; create an actual information packet; making bibliometric studies, etc. Librarians can also be conducted in their capacity as a manager of a journal. Librarians as journals managers may have the opportunity to network with members of other journal management associations, both nationally and internationally. Librarians can also actively assist other journals managers, particularly with regard to information technology systems used in the management of scientific journals. Librarians as research partners and civitas academica can apply their knowledge related to information literacy. Librarians can also help answer and handle any issues related to ISSN registration and journal management issues. The National Library needs to include the involvement of the librarian as a manager of the journal in one of the librarian's work. Especially when there is no special functional position that handles the management of scientific journals. The role of librarians as a manager of scientific journals should also be included in the competence of librarians as it relates to the expertise of librarians in providing information services. Thus, the active role of librarians in various institutions is expected to improve the quality of the management of scientific journals in Indonesia.